2018
DOI: 10.1016/j.immuni.2018.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Getting DAMP(s) Wets the Whistle for Neutrophil Recruitment

Abstract: Neutrophil recruitment in response to pathogen invasion is mediated through "self" tissue damage signals (DAMPs) and pathogen associated signals (PAMPs). In this issue of Immunity, Huang and Niethammer, (2018) demonstrate that DAMP signaling is a prerequisite for neutrophil recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…4a and S4A, B). These results were consistent with the previously observed ability of HMGB1 to mobilize neutrophils 26 . Importantly, the number of CD62L dim neutrophils was significantly increased in the 4T1-Conrtrol and EMT6-HMGB1 groups compared with that in the 4T1-shHMGB1 and EMT6-Control groups (Figs.…”
Section: Tumor Cell-derived Hmgb1 Is Responsible For Lung Metastasis supporting
confidence: 93%
“…4a and S4A, B). These results were consistent with the previously observed ability of HMGB1 to mobilize neutrophils 26 . Importantly, the number of CD62L dim neutrophils was significantly increased in the 4T1-Conrtrol and EMT6-HMGB1 groups compared with that in the 4T1-shHMGB1 and EMT6-Control groups (Figs.…”
Section: Tumor Cell-derived Hmgb1 Is Responsible For Lung Metastasis supporting
confidence: 93%
“…The host responds to both PAMPs and DAMPs by specific PRRs during infection, resulting in increased production of mediators and inflammatory response [33]. excessive inflammatory response induces organ injury.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of Trompette et al (2018) are complimented by recent study in Science by Zhao et al (2018). Zhao et al (2018) integrated human and mouse studies to show that a HFD selectively caused an increase in SCFA-producing bacteria that were associated with a significant reduction in symptoms associated with type 2 diabetes (T2D). In this study, control and treatment T2D patient groups received standard of care therapies supplemented with acarbose, an amylase inhibitor that increased the bioavailability of fermentable fiber to intestinal bacteria.…”
mentioning
confidence: 76%
“…Fascinatingly, in analysis of the HFDassociated microbiota, both Zhao et al (2018) and Trompette et al (2018) uncovered a significant enrichment for Bifidobacterium spp., a well-known producer of SCFAs. Zhao et al (2018) found that Bifidobacterium pseudocatenulatum correlated with improved HbA1c in T2D patients. Moreover, gavage of B. pseudocatenulatum in mice improved metabolic outcomes in a model of high-fat dietinduced obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation